Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I solve

$$a\cos^2(\theta) + b \sin^2(\theta) = 0$$

for $\theta$. Here $a,b$ are constants and $a \neq b, a \neq 0, b \neq0$.

I thought there might not be any solutions but with the constants $a,b,$ in front of them, I thought it is possible that they could be negative and the "right" constants to make the whole thing equal $0$.

So how would I solve this?

share|improve this question
1  
Use $\cos^2 + \sin^2 = 1$ –  Stefan Mar 20 '13 at 14:59
    
Your guess is right @Kaish . In some cases there may not be any soln. –  Abhra Abir Kundu Mar 20 '13 at 15:08

4 Answers 4

up vote 13 down vote accepted

Hint: Write $\cos^2\theta=1-\sin^2\theta$.

share|improve this answer

Your equation is $b \sin^2 \theta=-a \cos^2 \theta$ or $\tan^2 \theta=-\frac{a}{b}$

share|improve this answer

$a\cos^2(\theta) + b \sin^2(\theta) = 0$

$a(1-\sin^2(\theta)) + b \sin^2(\theta) = 0$

$a=(a-b)\sin^2\theta$

$\sin \theta=\sqrt{\frac{a}{a-b}}$ or $\sin \theta=-\sqrt{\frac{a}{a-b}}$

There will be a soln. iff $-1\le |\sqrt{\frac{a}{a-b}}|\le 1$

share|improve this answer

You could use the double-angle formulas $\cos^2 \theta = \frac{1+\cos(2\theta)}{2}$, $\sin^2 \theta=\frac{1-\cos 2\theta}{2}$. Substituting these into your equation gives $$ \frac{a+b}{2}+\frac{a-b}{2} \cos (2\theta)=0 \, , $$ which can easily be solved for $\theta$.

Of course, this is equivalent to the solutions using the Pythagorean identity. But it has the advantage that you've traded in all your squares for doubled angles, so you don't have to worry about square roots in your solution...

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.